Blended Learning Pembelajaran PAI - Aminulloh; SyamsulAripin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At the beginning of the pandemic, learning in the world of education in Indonesia turned becomes online learning withseveral problems felt by students and teachers, so that learning was re-implementation with face-to-face learning, so forthe first time used the blended learning model in learning. Based on that, our study explore deeply about “TheBlended Learning Model in Islamic Education Learning”. This study includes the planning, implementation, anddisadvantages and advantages of the blended learning model in Islamic Education. This Study used qualitative research method with case study type approach. This study shows that the planning of blended learning model is to form a blendedlearning teams, involving training related to the use of applications, prepare learning tools (RPP), learning materials and media, online assignments, and selections of learning application. The implementation model of blendedlearning in Islamic Education consisted of preliminary activities, core activities, and closing activities. Based on the result of the study, it was found that there were disadvantages dan advantages of the blended learning model inlearning Islamic Education.